Prevalence of Depression and Clinical Anxiety in Patients with Cardiovascular Disease - Martino, Pablo Luis; Mora-Penagos, Juan Pablo; Kerbage, Soraya; Cervigni, Mauricio Alejandro; Bonet, José Luis (Journal of Psychology and Psychotherapy Research, 2017)
Depression and Clinical Anxiety predict a worse prognosis for Cardiovascular Disease (CVD). Recent studies warn of high rates of clinical depression and anxiety in patients with CVD. The reported percentages range over a wide range. In order to provide new data on the prevalence of Depression and Clinical Anxiety in CVD, the psychological state of 70 Argentine adults attending a Cardiovascular Rehabilitation Program was surveyed. Two psychological scales were administered: the Beck Anxiety Inventory and the Beck Depression Inventory II. It was observed a 17.1% of participants with probable Major Depressive Disorder and a 27.1% with probable Clinical Anxiety. The results of the current study are in accordance with the percentages reported by previous studies. A significant number of patients presented comorbidity between Clinical Depression and Anxiety. No differences were found by gender. It is recommended that health professionals take into consideration the high prevalence of Clinical Depression and Anxiety in patients with CVD.